Analisis Sentimen Penggunaan Aplikasi Transportasi Online Pada Ulasan Google Play Store dengan Metode Naive Bayes Classifier - Dicki Nugraha; Dudih Gustian (LPPM STIKOM Tunas Bangsa, 2024)
Public transportation is a necessity for some people to carry out their daily activities. In the current digital era, public transportation can be accessed online using a smartphone through applications available on the Google Play Store, for example online transportation applications that are currently popular, namely Grab, Gojek, and Maxim. Since the application's new features, such as food shop services, online transportation applications have experienced an increase in the number of downloads. On the Google Play Store, usually before deciding to download an application, users often look at ratings and read reviews first. Because it has almost the same number of downloads and ratings, making the title the best application less relevant. To find out which online transportation application has the best title, a sentiment analysis was carried out on several online transportation applications on the Google Play Store. This user review analysis uses the Naïve Bayes Classifier (NBC) algorithm, which in several studies that have used this algorithm is considered to have a high enough level of accuracy so that it can determine the best online transportation application based on review comments on the Google Play Store. From the results of the analysis that has been carried out, it was found that the Gojek application got an accuracy value of 86%, the Grab application 87%, and the Maxim application got the highest accuracy level with a value of 93%.